Analisis Kasus Pencemaran Nama Baik Aaliyah Massaid di Media Sosial: Kajian Linguistik Forensik - Simatupang, Fitri Laura; Girsang, Elsalina; Sembiring, Kartika Patricia; Saragih, Mutiara; Sitorus, Lusiana; Gultom, Nicholay Hartawa; Siregar, Mustika Wati (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the defamation of Aaliyah Massaid which began with the spread of hoaxes on social media. Using a forensic linguistic approach, this study examines the narratives in posts accusing Aaliyah of being pregnant out of wedlock. Semantic, syntactic, and pragmatic analyses were conducted to reveal the implied meaning, sentence structure, and communicative effects of the narratives. The results of the analysis show that the narratives contain elements of slander, namely accusations without strong evidence and tend to degrade the dignity of individuals. In addition, this study also discusses the legal aspects of this case, namely violations of the ITE Law. Overall, this study highlights the negative impacts of the spread of hoaxes on social media and the importance of digital literacy in preventing similar cases.